Global Trend of International Cooperation and Its Implications for Nepal - Kharel, Hemanta (NCWA Annual Journal, 2026)
International cooperation is a very important tool in addressing global challenges, like poverty reduction, increasing economic growth, addressing climate change, pandemics, infectious diseases, migration, conflict, cross-border financial crimes, energy and food security, terrorism. Solving these issues is beyond the capability of any single country and call for joint efforts of the international community. The latest figure shows the composition of official assistance disbursement to Nepal; loans dominated with 86.85 percent of total aid, reflecting a growing dependence on debt-led financial aid. Grants accounted for about 14 percent, indicating limited non-repayable support. Nepal needs to maximize efforts to seek foreign assistance in grants and ensure that all loans are invested in productive sectors. Nepal needs to improve governance system for effective service delivery, to control rising corruption and slow aid delivery, which threatens donors’ willingness to continue and increase support.